2017
DOI: 10.1002/anie.201705190
|View full text |Cite
|
Sign up to set email alerts
|

Control of Ice Propagation by Using Polyelectrolyte Multilayer Coatings

Abstract: Ice propagation is of great importance to the accumulation of ice/frost on solid surfaces. However, no investigation has been reported on the tuning of ice propagation through a simple coating process. Herein, we study the ice propagation behavior on polyelectrolyte multilayer (PEM) surfaces coated with the layer-by-layer (LBL) deposition approach. We discover that ice propagation is strongly dependent on the amount of water in the outermost layer of PEMs, that is, the ice propagation rate increases with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 32 publications
(3 reference statements)
0
51
0
Order By: Relevance
“…Ice propagation is another factor causing ice deposition on the solid surface. [43] They studied the ice propagation behavior on polyelectrolyte multilayer (PEM) surfaces (Figure 4e). The ice propagation is strongly dependent on the amount of water in the outermost layer of PEMs.…”
Section: Ice Growth Patterns On Solid Surfacementioning
confidence: 99%
“…Ice propagation is another factor causing ice deposition on the solid surface. [43] They studied the ice propagation behavior on polyelectrolyte multilayer (PEM) surfaces (Figure 4e). The ice propagation is strongly dependent on the amount of water in the outermost layer of PEMs.…”
Section: Ice Growth Patterns On Solid Surfacementioning
confidence: 99%
“…Ice formation on surfaces is initiated with HIN and is then followed by ice propagation, which was investigated through layer‐by‐layer (LBL) depositing of a polyelectrolyte multilayer (PEM) on the surface . It was found that the ice‐propagation rate is governed by the amount of water in the outermost layer . Controlling the ice propagation could be another possible pathway to achieving anti‐icing .…”
Section: Interfacial Materials For Anti‐icingmentioning
confidence: 99%
“…[30] It wasf ound that the ice-propagation rate is governed by the amount of water in the outermost layer. [30] Controlling the ice propagation could be another possible pathway to achieving anti-icing. [31] In addition to delaying ice nucleation and retarding ice propagation throughl owering the HIN temperature and decreasing the ice-propagation rate, the observation of the formation of ice and organic crystals in pockets on naturally cleaved Muscovite mica, which acted like ice-nucleation active sites, was reported by Christenson et al [25d] Ac onfined phase forms along the apex of the wedge; subsequentg rowth out of the pockets generates twin bulk crystalsa si llustrated in Figure 4b, [25d] whichw as also observed by using opticalm icroscopy ( Figure 4c).…”
Section: Controlling Ice Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated earlier that ECIN nano‐thin films can be fabricated on a surface through electrostatic interactions using nonfood grade synthetic oppositely charged cationic poly (diallyldimethylammonium chloride) (PDDA) and anionic poly(styrenesulfonate) (PSS; Gezgin, Lee, & Huang, 2013). A similar work on ice propagation had been conducted using the layer by layer (LbL) deposition of polyelectrolyte pairs PSS/poly(allylamine hydrochloride) (PAH) and PSS/PDDA without using ECINs, where authors concluded that ice propagation can be tuned by modifying the outermost polymer layer (Jin, He, Guo, & Wang, 2017), which in fact was performed in our above cited work by adding a single layer of ECINs on the PSS/PDDA multilayers. We have also demonstrated the potential to fabricate the same using food grade charged biopolymers such as chitosan, carrageenan, and pectin (Gezgin, Lee, & Huang, 2017).…”
Section: Introductionmentioning
confidence: 99%